Geniposidic acid upregulates atrial natriuretic peptide secretion and lowers blood pressure in spontaneously hypertensive rats. (January 2018) - Nakamura, Kozo; Hosoo, Shingo; Yamaguchi, Shohei; Koyama, Masahiro; Yamazaki, Ryo; Hirata, Tetsuya; Yamaguchi, Yasuyo; Yamasaki, Hiroo; Minamino, Naoto; Wada, Keiji; Nishibe, Sansei
Highlights: GEA is an active ingredient of several medicinal plants. Single oral administration of GEA reduced SBP in male SHRs within 6 h. Oral GEA administration increased plasma levels of ANP, but not GLP-1, in SHR. GEA may act as a GLP-1 receptor agonist, thus promoting ANP secretion. Abstract: Geniposidic acid (GEA), the main ingredient of several medicinal herbs, has pharmacological effects on hypertension, inflammation, diabetes, atherosclerosis, and cancer. The current study evaluated the mechanism underlying the hypotensive effects of a single oral administration of 100 mg GEA/kg in male spontaneously hypertensive rats. Blood pressure was significantly reduced at 6 h post GEA treatment, as compared with control rats. Plasma levels of atrial natriuretic peptide (ANP) were also upregulated by GEA, indicating that its anti-hypertensive activity involved enhanced ANP secretion from cardiomyocytes. This could reflect GEA-mediated activation of glucagon-like peptide-1 (GLP-1) receptors on atrial cardiomyocytes. Plasma GLP-1 levels were not significantly altered by GEA. This study is the first to report that orally administered GEA produces beneficial effects on heart tissue by increasing plasma ANP levels, although GEA is a known GLP-1 receptor agonist. These effects could underlie the broad physiological effects of medicinal herbs containing GEA.